TECHNICAL EDUCATION IN THE CONTEXT OF THE LEARNERS´SPACE IMAGINATION DEVELOPMENT - TOMKOVA, Viera (Trends in education, 2011)
The issue dealt with in the paper is connected with the development of the learners´ basic competencies. The author concentrates on the development of the space imagination in the technical education. The space imagination in natural sciences and technical subjects is often the basis for the correct task solution. Development of the space imagination also stimulates the learners´ technical thinking which is inevitable in the technical task solution and in application of the technical creativity in project solutions.
Keywords: technical education; spatial imagination and technical thinking.